CTCF and ncRNA Regulate the Three-Dimensional Structure of Antigen Receptor Loci to Facilitate V(D)J Recombination - Choi, Nancy M.; Feeney, Ann J. (Frontiers in Immunology, 2014)
At both the immunoglobulin (Ig) heavy and kappa light chain loci, there are >100 functional variable (V) genes spread over >2 Mb that must move into close proximity in 3D space to the (D)J genes to create a diverse repertoire of antibodies. Similar events take place at the T cell receptor (TCR) loci to create a wide repertoire of TCRs. In this review, we will discuss the role of CTCF in forming rosette-like structures at the antigen receptor (AgR) loci, and the varied roles it plays in alternately facilitating and repressing V(D)J rearrangements. In addition, non-coding RNAs (ncRNA), also known as germline transcription, can shape the 3D configuration of the Igh locus, and presumably that of the other AgR loci. At the Igh locus, this could occur by gathering the regions being transcribed in the VH locus into the same transcription factory where Iμ is being transcribed. Since the Iμ promoter, Eμ, is adjacent to the DJH rearrangement to which one V gene will ultimately rearrange, the process of germline transcription itself, prominent in the distal half of the VH locus, may play an important and direct role in locus compaction. Finally, we will discuss the impact of the transcriptional and epigenetic landscape of the Igh locus on VH gene rearrangement frequencies.